Reviews of Books (International review of mission, 1962)
SEMANTICS IN THEOLOGICAL STUDY: THE SEMANTIC OF BIBLICAL LANGUAGES. By James Barr. CLASSICS OF THE CONTEMPLATIVE LIFE: ST JOHN CLIMACUS: THE LADDER OF DIVINE ASCENT. Translated by ARCHIMANDRITE LAZARUS MORRE with an Introduction by M. Heppell. CLASSICS OF THE CONTEMPLATIVE LIFE: SELECTED WRITINGS OF THE SPIRITUAL LIFE. Translated with an Introduction by Patricia McNulty. CLASSICS OF THE CONTEMPLATIVE LIFE: MEISTER ECKHART: SELECTED TREATISES AND SERMONS. Translated from Latin and German with an Introduction and notes by JAMES M. CLARK and JOHN V. SKINNER. INTRODUCING THE LITURGICAL REVIVAL: CHRISTIAN WORSHIP. By T. S. Garrett. THE CATECHUMENATE AND ITS PROBLEMS: DAS KATECHUMENAT IN DEN KATHOLISCHEN MISSIONEN. By Thomas Ohm. FOR THE NEW TESTAMENT STUDENT: A GREEK GRAMMAR OF THE NEW TESTAMENT AND OTHER EARLY CHRISTIAN LITERATURE. By F. Blass and A. Debrunner. Revised, translated and edited by ROBERT W. FUNK. MARRIAGE AND FAMILY LIFE: FAMILLIES ANCIENNES—FAMILLES NOUVELLES. THE DIMENSION OF THE PERSONAL: EDUCATION FOR MISSION. By J. Allan Ranck. THE WORKER-PRIEST MOVEMENT: PRIESTS AND WORKERS: AN ANGLO-FRENCH DISCUSSION. Edited by David L. Edwards. THE CHRISTIAN DIALOGUE WITH OTHERS RELIGIOUS: CHRISTIAN FAITH AND OTHERS FAITHS. By Stephen Neill. A HANDBOOK ON SUFISM: SUFISM, ITS SAINTS AND SHRINES: An introduction to the study of Sufism with special reference to India and Pakistan. (Revised Edition.) By John A. Subhan. REVELATION THROUGH IMAGERY: ALPHA AND OMEGA: A STUDY IN THE PATTERN OF REVELATION. By S. H. Hooke. MISSIONARY HISTORY IN PALESTINE: BRITISH INTERESTS IN PALESTINE, 1800–1901. A STUDY OF RELIGIOUS AND EDUCATIONAL. ENTERPRISE. By A. L. Tibawi. ALL ROUND SERVICE: EIN LEBEN FÜR SUDWESTAFRIKA: FESTSCHRIFT, Dr h.c. HEINRICH VEDDER. A MINISTRY OF SERVICE: DARE AND PERSEVERE: THE STORY OF ONE HUNDRED YEARS OF EVANGELISM IN SYRIA AND LEBANON, FROM 1860 TO 1960. By F. E. Scott. INTO THE HEART OF LEBANON: BUARU: PORTRAIT OF A LEBANESE MUSLIM VILLAGE. By Anne H. Fuller. CHURCH OF ENGLAND EXPANSION OVERSEAS: FRONTIERS OF THE CHURCH: THE MAKING OF THE ANGLICAN COMMUNION. By H. G. G. Herklots. OECUMENICAL PROFILES: OEKUMENISCHE PROFILE: BRÜCKENBAUER DER EINEN KIRCHE. GHOSTS FROM THE GREAT COLD MOUNTAINS: THE LOLO OF LIANG SHAN. By Lin Yueh-hua. CULTURE CHANGE AMONG THE PONDO: REACTION TO CONQUEST: EFFECTS OF CONTACT WITH EUROPEANS ON THE PONDO OF SOUTH AFRICA. By Monica Hunter. THE CHURCH IN AFRICA TO-DAY: L'EGLISE À L'HEURE DE L'AFRIQUE. By Guy Mosmans. SIGNIFICANT YEARS IN THE SUDAN: A HISTORY OF THE SOUTHERN SUDAN: 1839–1889. By Richard Gray. THE PROCESS OF DECOLONIZATION: BELGIAN ADMINISTRATION IN THE CONGO. By Georges Brausch. THE CHALLENGE OF COMPLEX PROBLEMS: TRAGEDY IN ALGERIA. By Gerard Mansell. MISSIONARY DATES AND THEIR SIGNIFICANCE: WICHTIGE DATEN DER MISSIONSGESCHICHTE: EINE ZEITTAFEL. By Thomas Ohm.